2016
DOI: 10.1093/icvts/ivw365
|View full text |Cite
|
Sign up to set email alerts
|

20 years experience with the Ross operation in middle-aged patients: the autologous principle is still alive

Abstract: The Ross operation in this cohort was associated with long-term survival similar to the general population and low incidence of reoperations. Patients with the preoperative diagnosis of AI are at increased risk for late autograft insufficiency and root dilatation. Decellularized allografts presented the best results for reconstruction of the RVOT. These results support the conclusion that the Ross operation has an important role in the treatment of middle-aged patients with aortic valve disease, especially tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…15,19,20 Our experience with decellularized allografts for RVOT reconstruction during the Ross operation in young adults has shown lower late peak gradients and the absence of calcification when compared with the conventional cryopreserved counterpart. 21,22 Similar results have been previously reported not only for the Ross operation but also for patients with congenital heart disease. 20,23,24 .However, these series include mostly older children and young adults.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…15,19,20 Our experience with decellularized allografts for RVOT reconstruction during the Ross operation in young adults has shown lower late peak gradients and the absence of calcification when compared with the conventional cryopreserved counterpart. 21,22 Similar results have been previously reported not only for the Ross operation but also for patients with congenital heart disease. 20,23,24 .However, these series include mostly older children and young adults.…”
Section: Discussionsupporting
confidence: 84%
“…This has already been demonstrated in our experience with decellularized allografts in young adults submitted to the Ross operation and now confirmed in the much more critical subgroup of children below 12 years of age. 21,22 Not less important, is the fact that decellularized allografts proved very resistant to infections, with no documented or suspected case of bacterial endocarditis in our series.…”
Section: Discussionmentioning
confidence: 69%
“…These series reinforce previously published results showing low hospital mortality and excellent long-term survival with the Ross operation ( 17 , 19, 20 ). One of its advantages is the diminished risk of thromboembolism and no need for anticoagulation which impacts positively on quality of life ( 21 , 22 ).…”
Section: Surgical Optionssupporting
confidence: 91%
“…These numbers vary considerably depending on patient diagnosis, age and procedure. For example, patients who underwent the Ross procedure had 92% freedom from reintervention after 16 years (Da Costa et al 2017), while a young patient group (\ 1 year) with more complex diagnoses showed 38% freedom from reintervention after 10 years (Vitanova et al 2014). When collecting and preparing a homograft, several aspects have to be considered.…”
Section: Introductionmentioning
confidence: 99%